Inequality in Pre-Industrial Urban Bohemia: The City of Budweis - Daniel Kolar (Charles University in Prague, Institute of Economic Studies (IES), 2021)
Motivated by the lack of previous research on historical inequality in Central Europe, this paper constructs wealth inequality statistics for a larger town in South Bohemia, Budweis. The data sources are rare detailed local tax censuses from 1416 and 1523 and a national tax register from 1654 as reported in the literature, further adjusted for lowest social groups and processed to create social tables. If the underlying data are accurate, the wealth inequality Gini coefficient in 1416 was between 0.739 and 0.777. The estimated wealth share of the top 1% evolved from 22.6% in 1416 to 9.6% in 1654, values significantly lower than in the pre-industrial UK or France, as well as in the contemporary Czech Republic.
Keywords: N33; N43; N93; D63; 330; historical inequality; social tables; Gini coefficient; wealth